2016
DOI: 10.1089/apc.2016.0143
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Nonlipid Cardiovascular Disease Risk Factor Management in the Women's Interagency HIV Study and Association with Adherence to Antiretroviral Therapy

Abstract: Cardiovascular disease (CVD) is increasingly common among women with HIV, but literature on nonlipid CVD risk factor management is lacking. We examined semiannual trends from 2006 to 2014 in hypertension treatment and control (blood pressure <140/90 mmHg), diabetes treatment and control (fasting glucose <130 mg/dL), and smoking quit rates in the Women's Interagency HIV Study. Unadjusted and adjusted Poisson regression models tested time trends and differences between HIV+ and HIV-women. Among antiretroviral th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Suboptimal cardiovascular risk management has been previously reported both in the general and HIV-positive population. 5 , 7 13 , 18 , 19 , 21 26 These studies in HIV-positive populations had smaller proportions of individuals with suppressed viraemia on cART and often focused on one aspect of cardiovascular risk management, whereas our study assessed management more comprehensively. Although over 90% of HIV-positive individuals in our study population had suppressed viraemia – and were thus adherent to cART – we found it striking that (effective) use of cardiovascular medication was poor.…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal cardiovascular risk management has been previously reported both in the general and HIV-positive population. 5 , 7 13 , 18 , 19 , 21 26 These studies in HIV-positive populations had smaller proportions of individuals with suppressed viraemia on cART and often focused on one aspect of cardiovascular risk management, whereas our study assessed management more comprehensively. Although over 90% of HIV-positive individuals in our study population had suppressed viraemia – and were thus adherent to cART – we found it striking that (effective) use of cardiovascular medication was poor.…”
Section: Discussionmentioning
confidence: 99%
“…A US WIHS study suggested that a higher percentage of WLHIV receive targeted therapeutics for known cardiometabolic risk factors as compared with women without HIV(73). In contrast, a US Partners Healthcare System database study revealed that a lower percentage of WLHIV with heart failure were prescribed standard-of-care therapy as compared with uninfected women with heart failure(9).…”
Section: Sex-specific Mechanisms Underlying Heightened Cvd Risk Amongmentioning
confidence: 99%
“…In contrast, a study from the Women’s Interagency HIV Study (WIHS) cohort showed HIV-infected women to have better controlled hypertension and diabetes compared with HIV-uninfected women. 90 …”
Section: Management and Prevention Of Ischemic Heart Disease In Hivmentioning
confidence: 99%